A new endoprosthesis with sensing capability - Isa C.T. Santos (2010)
An aneurysm is a severe health condition with high impact in human life. One of its current treatments is endovascular aneurysm repair, a minimally invasive surgery in which a stent-graft is guided, from the femoral artery to the affected segment, in order to prevent wall rupture. Stent-grafts are endoprosthesis composed of a metallic scaffold and a polymeric covering membrane. While early devices were made from stainless steel stents and woven polyester grafts, nowadays other materials are being used. The devices performance has been improved by the introduction of new materials; nevertheless, literature shows that more can be done. This article reviews the design of some thoracic home-made stent-grafts as well as the commercial devices available both in Europe and in the USA. Additionally, future trends concerning the development of this type of devices are presented, including the design of a new endoprosthesis with an embedded flexible pressure sensor.